Adipocitocinas em portadores da forma indeterminada da doença de Chagas e dislipidemia - Navarro, Elaine Cristina [UNESP] (2013)
This study aimed at estimating the number of cases of non-negative serological reactions to Chagas disease in blood donors at the Blood Center of Botucatu, São Paulo – Brazil from 2003 to 2010 and at relating them to their cities of origin. Five hundred and seventy-four non-negative results for Chagas disease were evaluated. Of these, 371 (64.8%) were reagent, and 203 (35.4%) were inconclusive. There were, on average, 72 cases/year, and a prevalence of males was observed (64.8%). Forty-three (7.49%) individuals were 18 to 30 years old; 92 (16.02%) were 31 to 40; 147 (25.61) 41 to 50, and 292 (50.87%) were older than 50 years. It was observed that 29.3% of females with reagent serology were at their fertile age (18 and 45 years). The majority of donors were originally from cities in the southwestern and central regions of São Paulo, but individuals from other states contributed with 20%. The provenance of most donors was the city of Botucatu/SP, followed by the city of Taquarituba/SP. Therefore, the profile of donors at this blood center favors the occurrence of a larger number of non-negative serological reactions. Although there has been a significant reduction in the number of new cases/year for this disease, it is still a public-health problem, and results suggest the need for new epidemiological assessments in the studied region